2019
DOI: 10.1097/ncm.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Spiritual and Religious Influences in Care Delivery

Abstract: Purpose: The impact of spiritual and religious factors on health and care delivery has been identified in case management field research. The purpose of this article is to examine how case managers, taking a holistic, patient-centered approach, are required under professional and ethical standards to address the spiritual and religious influences that may impact the individual's health, care choices, and care delivery. Primary Practice Settings: Case ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Such competence and sensitivity require a dental health-care professional to respect the religious and cultural practices in health-care delivery to avoid violating beliefs and practices. [ 10 ] However, this might not be due to a lack of respect but rather a lack of knowledge of the grafting material source. In one study by Enoch et al (2005), a highly significant number of surveyed health-care workers did not know all the products’ constituents correctly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such competence and sensitivity require a dental health-care professional to respect the religious and cultural practices in health-care delivery to avoid violating beliefs and practices. [ 10 ] However, this might not be due to a lack of respect but rather a lack of knowledge of the grafting material source. In one study by Enoch et al (2005), a highly significant number of surveyed health-care workers did not know all the products’ constituents correctly.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the impact of religious practices and adherence to religious and cultural traditions may directly impact choices and influence treatment decisions. [ 10 ] In 2013, Ericson et al surveyed religious and spiritual leaders of the six largest religions worldwide on the issue of human- and animal-derived products, and they indicated that it is a necessity to obtain informed consent specifically for any animal- or human-derived products for several religions since they may oppose the treatment. However, some religious groups may find some acceptable materials tolerable if there are no alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, spirituality exists in nearly all patients; however, it varies by culture, religion, and socioeconomic status (LeDoux et al, 2019 ). Improving the spiritual dimension of stroke patients can improve their health (Steigleder et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying barriers and facilitators of adherence to therapy and their relationships with patient awareness, beliefs, and values can help the pharmacist in optimising the management of culturally and religiously oriented groups of patients 13,14 including those living in rural areas. This brings us to the aim of this study, which is to investigate perspectives of patients diagnosed with psychiatric disorders, living in rural areas in Jerash, Jordan, regarding their awareness about their psychiatric conditions and their treatment, adherence to their treatment, and related barriers, with special focus on the pharmacist's role.…”
Section: Introductionmentioning
confidence: 99%